ICAM1 and VCAM1 are associated with outcome in patients with sepsis: A systematic review and meta-analysis - Jiawei He; Meili Duan; Haizhou Zhuang (Heliyon)
Background: Endothelial cell dysfunction and microcirculatory disturbances play crucial roles in the pathogenesis of sepsis. This systematic review and meta-analysis explored the relationship of the plasma levels of the key endothelial proteins intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) with clinical outcomes in patients with sepsis. Methods: MEDLINE and EMBASE were searched through November 28, 2023. ICAM1 and VCAM1 levels and patient outcomes were evaluated. The primary outcome was the relationship of sepsis with ICAM1 or VCAM1. The secondary outcomes were the relationships of septic shock and multiple-organ dysfunction syndrome (MODS) with ICAM1 and VCAM1. Variables were compared using standardized mean differences (SMDs) with 95 % confidence intervals (CIs). Results: Forty-one studies were included. ICAM1 (SMD = 1.12, 95 % CI = 0.67, 1.57; P < 0.00001) and VCAM1 (SMD = 0.65; 95 % CI = 0.17, 1.13; P = 0.008) were associated with sepsis. Similarly, both ICAM1 (SMD = 2.30; 95 % CI = 1.30, 3.31; P < 0.00001) and VCAM1 (SMD = 0.93; 95 % CI = 0.27, 1.59; P = 0.006) were associated with MODS. ICAM1 was associated with septic shock (SMD = 1.93; 95 % CI = 0.55, 3.30; P = 0.006), overall mortality (SMD = −1.18; 95 % CI = −1.76, −0.61; P < 0.0001), and sepsis-related mortality (SMD = −0.64; 95 % CI = −0.88, −0.39; P < 0.00001). VCAM1 was associated with overall mortality (SMD = −0.71; 95 % CI = −1.02, −0.40; P < 0.00001), sepsis-related mortality (SMD = −0.62; 95 % CI = −1.14, −0.10; P = 0.02), and MODS-related mortality (SMD = −0.55; 95 % CI = −0.89, −0.21; P = 0.002). Conclusion: Elevated plasma ICAM1 and VCAM1 levels could increase the risks of sepsis, septic shock, MODS, and mortality.